Integrating TPACK for Soft Skills and Communication in Engineering Education: Definition, Concept, Strategies, Challenges, and Opportunities - Shinde, Sunanda M.; Shinde, Mahesh B. (Universitas Pendidikan Indonesia (UPI), 2025)
Soft skills and communication are essential for engineering students but are often overlooked in technical education because of the heavy focus on subject knowledge. This review explored how the Technological Pedagogical Content Knowledge (TPACK) framework can enhance the teaching of communication and soft skills in engineering education. Using a systematic review approach, this study analyzed concepts and definitions, according to relevant research. We also incorporated insights from a Lecture Series conducted for first-year engineering students. The review found that TPACK effectively integrated communication content, pedagogy, and technology to create interactive and engaging learning environments. However, challenges such as limited technological readiness among teachers, low student motivation, and insufficient institutional support hindered its implementation. Because engineering graduates require both technical and communication competencies, integrating TPACK offers a practical solution to bridge this gap. This review provided strategies and recommendations to help educators and institutions strengthen soft skills instruction in engineering programs to meet future workforce demands.